2018
DOI: 10.3389/fphar.2018.00456
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of South African Plants as a Unique Resource for Bioactive Endophytic Microbes

Abstract: South Africa has a long history and strong belief in traditional herbal medicines. Using ethnobotanical knowledge as a lead, a large number of South African medicinal plants have been discovered to possess a wide spectrum of pharmacological properties. In this review, bioprospecting of endophytes is highlighted by following the advantages of the ethnomedicinal approach together with identifying unique medicinal plants where biological activity may be due to endophytes. This review focuses on the current status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 129 publications
0
7
0
1
Order By: Relevance
“… 51 Afolabi et al 52 further reported that many people attest to being cured after consuming herbs and vegetable leaves. Abdalla and McGaw 53 assert that using natural products has a long history in human existence.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“… 51 Afolabi et al 52 further reported that many people attest to being cured after consuming herbs and vegetable leaves. Abdalla and McGaw 53 assert that using natural products has a long history in human existence.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A política de bioeconomia da África do Sul descreve a utilização econômica de sua biodiversidade como uma estratégia de desenvolvimento nacional, a Economia da Biodiversidade [43] . Como um dos poucos megadiversos países com grupos tradicionais de conhecimento etnobotânico relacionado à medicina de plantas, a biodiversidade da África do Sul é uma promessa econômica considerável [43,44] . A economia da biodiversidade da África do Sul tem dois componentes principais: a Economia Wildlife, a qual relaciona-se com a criação e a venda de animais; e a Economia de Bioprospecção, que diz respeito à exploração econômica de recursos biológicos e não animais, incluindo recursos genéticos no cultivo, coleta, processamento, fabricação e na exportação de produtos naturais em setores de mercado e varejo, como cremes, pomadas e suplementos nutricionais, por exemplo, o que demonstra que a Economia de Bioprospecção da África do Sul pode ser considerada parte dos setores relacionados à saúde e ao comércio do país.…”
Section: ) áFrica Do Sulunclassified
“…Plants with ethnobotanical historical use in treating certain diseases are promising candidates for obtaining bioactive compounds to control high-activity endophytic fungi (Strobel and Daisy 2003;Abdalla and McGaw 2018). The current prospect of bioactive compounds and the high demand for medicinal ingredients have spurred the search for new bioactive metabolites inside medicinal plant endophytic fungi (Zhao et al 2010).…”
Section: Introductionmentioning
confidence: 99%